Association between social frailty and quality of life in older patients with chronic heart failure: sequential multiple mediating effects of family insufficiency and social networks - Junting Huang; Xiaobo Liu; Duolao Wang; Xiaorong Luan; Wanxia Yao (Frontiers in Medicine)
Background and objectivesOlder patients with chronic heart failure have severe somatic symptoms, which lead to high levels of social frailty and loss of quality of life. Understanding the demographic and disease factors of quality of life and its relationship with social frailty is beneficial to overall health for older patients with chronic heart failure. This study aims to explore the relationship between social frailty and quality of life in older patients with chronic heart failure and to verify whether family insufficiency and social networks moderate this relationship.MethodsA multi-centre cross-sectional study was conducted on 443 older patients with chronic heart failure from three tertiary hospitals in China. The study questionnaire included a general information questionnaire, the HALFT scale (social frailty), the Family APGAR Index (family insufficiency), the LSNS-6 (social networks), and the MLHFQ (quality of life). Hierarchical regression analysis was used to assess the factors influencing quality of life; the SPSS PROCESS Marco Plug-in was employed to conduct mediation analysis.ResultsThe results showed that age, the number of hospitalizations, and NYHA classification influenced the quality of life in older patients with chronic heart failure. Social frailty, family insufficiency, and social networks were related, and family insufficiency and social networks mediated the relationship between social frailty and quality of life, with mediating effect sizes of 25.87, 99.5 and 58.97%, respectively.ConclusionThis study shows that high levels of social frailty are associated with reduced quality of life in older patients with chronic heart failure. Decreasing family insufficiency and extending social networks help alleviate social frailty’s adverse effects on the quality of life in older patients with chronic heart failure.